Implementasi Hasil Belajar PAI Dalam Lingkungan Keluarga di Desa Kertagena Tengah Kecamatan Kadur Pamekasan - sayyi, ach; Laili, Moh (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
The issue of implementing Islamic Religious Education learning outcomes in a family environment is a familiar thing, even we can find it almost every day. This problem is a complex problem, so it is necessary to look for any obstacles they face. If the constraints are known, a solution must be found. So that this problem does not become a prolonged problem and will lead to other problems. Actualization of Islamic Religious Education learning outcomes in Kertagena Tengah Village Kadur Subdistrict Pamekasan Regency in the family environment is not in line with the expectations of parents. This is caused by factors of the child's self and environmental factors. As can be seen from the declining morals and morals of students/ children, the lack of respect for children to parents at home, as well as the fading attitude of empathy and feeling of time for the suffering of others. For this reason, researchers look for factors that cause these problems. Lazy and lack of self-confidence, lack of attention and communication between children and parents, lack of motivating children towards learning and not supported by complete facilities and infrastructure is a picture of the unsuccessful implementation of Islamic religious education learning outcomes in the family environment. Provide motivation to children, provide exercises or guidance either by understanding verbally or actions (practice), providing complete facilities, and maintaining good relations/ communication with children. give praise/ prizes for children who excel, give examples of good learning, and maintain the familiarity / attention of parents with children. It is expected to be able to change the mindset of students towards their personality or behavior in the family